2002
DOI: 10.1176/appi.ajp.159.10.1738
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Care for Depression in Patients With Comorbid Medical Illness

Abstract: Depressed patients with comorbid medical disorders tend to have similar rates of treatment but worse depression outcomes than depressed patients without comorbid medical illness. Quality improvement programs for depression can improve treatment rates and outcomes for depressed primary care patients with comorbid medical illness. The authors discuss the implications of these findings for clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 33 publications
1
74
4
Order By: Relevance
“…For example, Bogner and colleagues found that, compared to patients without heart disease, patients with heart disease were more likely to be identified as depressed by the primary care physician, but less likely to be actively managed for depression. 29 Koike and colleagues found that rates of depression treatment in patients with medical disorders who participated in a quality improvement program were low despite the greater severity of depression. 30 In summary, such studies demonstrate patterns of practice that downplay the importance of treating depression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bogner and colleagues found that, compared to patients without heart disease, patients with heart disease were more likely to be identified as depressed by the primary care physician, but less likely to be actively managed for depression. 29 Koike and colleagues found that rates of depression treatment in patients with medical disorders who participated in a quality improvement program were low despite the greater severity of depression. 30 In summary, such studies demonstrate patterns of practice that downplay the importance of treating depression.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, it is widely advocated that major depression must be appropriately and aggressively treated in patients with chronic somatic disease (Sutor et al 1998 ;Whooley & Simon, 2000 ;Cassano & Fava, 2002). Indeed, appropriate treatment has been found to improve both the course and outcome of depression and the co-morbid somatic disease as well as patient quality of life (Maier & Falkai, 1999 ;Koike et al 2002;Stockton et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…82 Organized follow-up programs that include patient education, telephone or in-person contact every 2 to 4 weeks, monitoring of medication adherence, and psychiatric consultation as necessary improve outcomes for depressed cardiac patients. [83][84][85][86] "Measurement-based care," which uses frequent ratings of symptoms and adverse effects to guide dose adjustments and changes in treatment, can also be of benefit. 87 If antidepressant medication does not improve symptoms by 4 weeks and adverse effects are tolerable, the initial medication dose should be doubled.…”
Section: How Should Cardiac Patients Be Followed Up After Initiating mentioning
confidence: 99%